2006
DOI: 10.1111/j.1439-0507.2006.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

First case report of empyema caused by Beauveria bassiana

Abstract: Infections with Beauveria bassiana are extremely rare in humans. A 51-year-old man was admitted to hospital with the diagnosis of lung adenocarcinoma. Thoracic wall resection with lobectomy was applied and empyema has developed after prolonged air leakage. B. bassiana was isolated in pleural fluid. The patient improved without antifungal therapy after thoracotomy with securing of air leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…1,5,10 Two of these cases were in severely immunocompromised patients. 5,10 A B. bassiana empyema described in an immunocompetent patient responded to drainage without antifungal therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5,10 Two of these cases were in severely immunocompromised patients. 5,10 A B. bassiana empyema described in an immunocompetent patient responded to drainage without antifungal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…1 Three case reports of B. bassiana keratitis have been reported previously, 2 requiring surgical extirpation and 1 responding to medical therapy. [2][3][4] We report a case of B. bassiana keratitis with confocal and histologic smear findings failing multiple topical and systemic antifungal medications and treated successfully with the addition of oral posaconazole to topical voriconazole.…”
mentioning
confidence: 99%
“…This correlates with a case report from Turkey describing a patient who underwent a thoracic wall resection with lobectomy and developed a postoperative empyema attributed to B. bassiana. 25 Beauveria and other fungi are used as biopesticides worldwide. In a review article about human exposure to fungi used in biocontrol agents, Madsen et al 1 report that Beauveria has been found in indoor environments, is often isolated from insects and soil samples, and because conidia are presumably dispersed by air currents, it may occur in air where insect hosts live.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of airborne saprophytic fungi causing invasive disease in individuals who otherwise have a healthy immune system is low. However, for those with pre-existing conditions, the potential for a disease to arise is quite high (Gürcan et al, 2006). Thus this is why it is imperative that the fungal concentration in such highly populated buildings such as hospitals (Sarica et al, 2002), schools (Hargreaves, 2003) and pre-school crèche facilities (Aydogdu and Asan, 2008) is researched.…”
Section: Discussionmentioning
confidence: 99%